MODEL MANAJEMEN MUTU TERPADU BERBASIS MULTIPLE INTELEGENCE PADA SEKOLAH DASAR UNGGULAN DI KABUPATEN JEPARA - Setiardi, Dicky; Munir, Muhammad Misbahul (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2018)
This research is a study of qualitative descriptive. It was carried out at the Jepara Bumi Kartini Primary School. The instrument technique used to collect the data is by interviewing, observing and documentation. The prominent resources is headschool respon, teachers, employees,committee, and the organization of management in primary school of Unggulan Terpadu Bumi Kartini, that collected by essay document, video record/audio tape/MP3 and documetation.  The data analysis was carried out at the preliminary study stage, data development and validation stages.The results of the study showed that the application of integrated quality management based on multiple intellegence in the Primary School of Unggulan Bumi Kartini of Jepara Kartini was more aim towards mathematical logical intelligence. Several efforts can be done to implement integreted quality management based on multiple intellegence in other intelligences is by synergizing in the form of good management governance including the availability of human resources, availability of facilities and infrastructure, a conducive environment, updated curriculum, as well as the role of school committees and society participation in implementing integrated quality management based on multiple intellegence, so as to improve the quality of students who will ultimately create excellent schools.